Pharmacological targeting of ferroptosis in hypoxia-induced pulmonary edema: therapeutic potential of ginsenoside Rg3 through activation of the PI3K/AKT pathway - He, Yacong; Wang, Yilang; Duan, Huxinyue; Huang, Demei; Jia, Nan; Shen, Zherui; Wang, Zhenxing; Wang, Mingjie; Zhao, Tianzhu (Frontiers in Pharmacology, 2025)
BackgroundHigh-altitude pulmonary edema (HAPE), a severe manifestation of hypoxia-induced pulmonary hypertension, continues to present a major health concern in high-altitude environments due to the absence of efficient preventive measures. This investigation explores the protective influence of ginsenoside Rg3 (G-Rg3), an active substance derived from the botanical drug Panax ginseng C.A.Mey., on the prevention of HAPE progression.MethodsA mouse model mimicking exposure to 6000-m altitude (n = 63 C57BL/6 mice) was employed to evaluate the impact of G-Rg3 (15/30 mg/kg) using histopathological, biochemical, and multi-dimensional molecular assessments. Western blotting, network pharmacology and computational simulations were utilized to identify molecular targets of G-Rg3. The role of the PI3K/AKT signaling pathway was further validated through experiments using the PI3K/AKT inhibitor LY294002.ResultsPre-treatment with G-Rg3 effectively alleviated HAPE, maintained the stability of lung ultrastructure, and inhibited inflammatory mediators and oxidative stress indicators. Mechanistically, G-Rg3 prevented ferroptosis by stimulating the PI3K/AKT signaling pathway, as evidenced by the upregulation of protective proteins (GPX4, Nrf2, HO-1, SLC7A11, FTH1, FLC) and the downregulation of iron metabolism regulatory factors (TFRC, COX2). Network pharmacology and molecular docking analysis confirmed that PI3K/AKT is the core target of G-Rg3, and the protective effect disappeared when this pathway was inhibited. G-Rg3 uniquely regulated oxidative stress and inflammation by inhibiting ferroptosis, demonstrating adaptability to high-altitude environments.ConclusionThis research examined the pharmacological impacts and molecular pathways of ginseng active monomers on HAPE, suggesting the potential of G-Rg3 as a promising treatment option for this condition.